A recurrent rare intronic variant in CAPN3 alters mRNA splicing and causes autosomal recessive limb‐girdle muscular dystrophy‐1 in three Pakistani pedigrees. Issue 2 (25th October 2021) - Khan, Kamal; Mehmood, Sarmad; Liu, Chunyu; Siddiqui, Maimoona; Ahmad, Arsalan; Faiz, Belqees Yawar; Chioza, Barry A.; Baple, Emma A.; Ullah, Muhammad I.; Akram, Zaineb; Satti, Humayoon S.; Khan, Raees; et al.
Abstract: Autosomal recessive limb‐girdle muscular dystrophy‐1 (LGMDR1) is an autosomal recessive disorder characterized by progressive weakness of the proximal limb and girdle muscles. Biallelic mutations in CAPN3 are reported frequently to cause LGMDR1. Here, we describe 11 individuals from three unrelated consanguineous families that present with typical features of LGMDR1 that include proximal muscle wasting, weakness of the upper and lower limbs, and elevated serum creatine kinase. Whole‐exome sequencing identified a rare homozygous CAPN3 variant near the exon 2 splice donor site that segregates with disease in all three families. mRNA splicing studies showed partial retention of intronic sequence and subsequent introduction of a premature stop codon (NM_000070.3: c.379 + 3A>G; p.Asp128Glyfs*15). Furthermore, we observe reduced CAPN3 expression in primary dermal fibroblasts derived from an affected individual, suggesting instability and/or nonsense‐mediated decay of mutation‐bearing mRNA. Genome‐wide homozygosity mapping and single‐nucleotide polymorphism analysis identified a shared haplotype and supports a possible founder effect for the CAPN3 variant. Together, our data extend the mutational spectrum of LGMDR1 and have implications for improved diagnostics for individuals of Pakistani origin.